The Effect of Goverment Policy and Market Failure on Divergence of Cassava Competitiveness in South Lampung - Abriani, Dwika Mutiara; Lestari, Dyah Aring Hepiana; Haryono, Dwi (Jurnal Manajemen & Agribisnis, 2023)
Indonesia is one of the world's leading cassava producers, and Lampung Province is the main producer. Efforts to increase cassava production must be accompanied by good farming activities that link to a complete agribusiness system. This study aims to analyze the divergence effect of cassava competitiveness as an effect of government policies and market failure in South Lampung. This study was conducted using a survey method. The number of respondents was 64 cassava farmers, 8 cassava collectors, and 1 tapioca industry. Data collection was carried out in August-September 2022. This study uses PAM (Policy Analysis Matrix) to analyze the competitiveness and the divergence effect and market structure analysis to analyze the market failure. The result showed that there is a market failure of cassava because the market structure is not perfectly competitive (oligopsony). Therefore, the divergence effect of cassava did not reach the target because it caused the transfer of inputs prices from traders to farmers due to the fertilizer subsidy and the transfer of income from consumers to farmers due to the determination of cassava minimum price (Rp900/kg). However, cassava farming has a competitiveness with the value of comparative advantage (DRCR = 0.3091) which is smaller than the value of competitive advantage (PCR = 0.5865). The changes from comparative to competitive advantage require government policies to control market failure and to reduce the high transaction cost economy. Keywords: divergence effect, market failure, cassava, oligopsony, agribusiness system